2018
DOI: 10.1042/cs20171523
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuates effects of cyclophilin A on macrophages, reduces lipid uptake and secretion of cytokines by repressing decreased AMPK activity

Abstract: Growing evidence implicates cyclophilin A secreted by vascular wall cells and monocytes as a key mediator in atherosclerosis. Cyclophilin A in addition to its proliferative effects, during hyperglycemic conditions, increases lipid uptake in macrophages by increasing scavenger receptors on the cell's surface. It also promotes macrophage migration across endothelial cells and conversion of macrophages into foam cells. Given the known effects of metformin in reducing vascular complications of diabetes, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…As shown in Figure a, compared with the ox‐LDL group, the expression of SIRT1 was significantly increased by TASAES pretreatment. Previous study had reported that ox‐LDL could decrease AMPK activity (Ramachandran et al, ). Therefore, we investigated the protective effects of TASAES on ox‐LDL‐induced AMPK phosphorylation.…”
Section: Resultsmentioning
confidence: 96%
“…As shown in Figure a, compared with the ox‐LDL group, the expression of SIRT1 was significantly increased by TASAES pretreatment. Previous study had reported that ox‐LDL could decrease AMPK activity (Ramachandran et al, ). Therefore, we investigated the protective effects of TASAES on ox‐LDL‐induced AMPK phosphorylation.…”
Section: Resultsmentioning
confidence: 96%
“…Several putative atheroprotective mechanisms of metformin have been reported. Cell and animal studies have demonstrated that metformin favorably modulates secretion of proinflammatory cytokines and AMP-activated kinase (AMPK) implicated in atherogenesis (4)(5)(6). Metformin has also been shown to enhance the functional activities of high-density lipoprotein (HDL) (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that CyPA was a good marker for early detection of renal changes in DN. 5,24,[36][37][38][39] The present study describes the rising urinary CyPA in diabetic rats. We tried to find out the possibility of using the urinary CyPA as a new marker for diagnosis of DN as early as possible.…”
Section: Discussionmentioning
confidence: 78%